E-010 Prolonged Neurologic Deterioration Following Acetazolamide Testing in the Acute Phase Following Ischaemic Stroke. (14th July 2013) - Tawk, R; Eidelman, B; Hanel, R; Meschia, J; Barrett, K
Abstract : Background: Acetazolamide induces cerebral vasodilatation and may be used to measure cerebrovascular reserve in patients with cerebral arteriopathy. While acetazolamide is known to induce transient neurologic deficits as a result of "steal phenomenon, " prolonged deficits have rarely been described. Methods: Retrospective, single-centre case review from 2011 to 2012. Results: We describe 3 patients ages 41, 60 and 65 years (2 women; 1 man) who developed prolonged neurological deterioration following administration of acetazolamide in the acute phase following presentation for evaluation of cerebrovascular reserve. Two patients presented with hemispheric ischaemic symptoms; one presented with headache and parietal convexity subarachnoid haemorrhage. One patient had extensive intracranial vascular disease consistent with a moyamoya-like syndrome with left middle cerebral artery (MCA) occlusion and severe left supraclinoid internal carotid artery (ICA) stenosis. Another had 50% left MCA stenosis as well as > 70% stenosis of the left ICA. She failed medical therapy, L CAS, L MCA angioplasty, and left EC-IC bypass. A third patient had occlusion of the right ICA and severe left ICA stenosis. In every case, acetazolamide challenge was carried out in the acute phase following presentation. All three patients developed significant prolonged worsening of neurologic deficits following the administration of acetazolamide (1 g). Patients received aggressive intravenous hydration. Two of the patients regained pre-acetazolamide neurological status within 18 hours. The third patient recovered several days after emergency left carotid artery stenting. Imaging studies (CT in 2 cases; MRI in 1) did not reveal interval haemorrhage or additional ischaemic changes in any case. Conclusion: Administration of acetazolamide has the potential to induce decline in neurological function after administration in the acute phase and may be persistent for several hours or days. A steal phenomenon is a possible mechanism. The combination of severe extracranial and intracranial vascular disease may predispose to prolonged deficits and may be a contraindication to diagnostic use of acetazolamide. Disclosures: R. Tawk: None. B. Eidelman: None. R. Hanel: None. J. Meschia: None. K. Barrett: None.